Microhardness According to Surface, Distance and Time of Photopolymerization of a Bulk-Fill Resin: In Vitro Study - Loayza-Gallegos, María José (2026)
This study compared Vickers microhardness (VHN) according to the surface, distance and time of photopolymerization (PP) of Tetric® N-Ceram Bulk Fill (TNCBF). An in vitro study was performed of 80 cylindrical samples (4 mm×4 mm) randomly distributed into 8 groups according to distance (0 and 3 mm) and time (10, 20, 30, 40 s) of LED PP 1470 mW/cm2. The depth of cure was adequate when the ratio of tripled VHN (Kg/mm²) between lower/upper surfaces was>0.8. Statistical analysis was performed with the three-way ANOVA test with post hoc Tukey and Tamhane (p<0.05). The effect on VHN was highly significant when individually analyzed by the surface, time and distance of PP and interaction time × distance of PP (p<0.001). The average depth exceeded 80% of VHN regardless of the distance and time of PP. The VHN was higher at a distance of 0 mm compared to 3 mm at 10 and 20 s of PP regardless of the surface (p<0.001). The VHN was similar at all times with a PP distance of 0 mm (p≥0.377) and increased at 20 s with a PP distance of 3 mm (p≤0.001). The surface, distance and time of PP affected the hardness of TNCBF, which can have an impact on its clinical performance. The depth of cure using VHN results were favorable with 20 s of PP at a distance of 0 mm for a thickness of 4 mm of TNCBF.